Gejala Bahasa pada Penulisan Istilah Keagamaan dan Kata Serapan dari Bahasa Arab - Ramlan Abdul Gani (Refleksi: Jurnal Kajian Agama dan Filsafat, 2022)
This research attempted to explain how the phenomenon of writing in religious terms and cognate from Arabic, which is usually used in interpretation science and hadith or Islamic Study. The sample was found from college student writing. There were at least 500 words found in Arabic. It can be concluded that there are four indications of cognate used in religious terms consists of analogy, hypercorrection, adaptation, and metathesis. The vocabulary in original Arabic words (without being changed). This is found because the writer regards the term sacred value. If that word change into the Indonesian language, the word or that term loses sacred value.